(untitled) (Journal of the College of Basic Education, 2022)
The media is one of the seven criteria set by (De Bogrand) and (Desler) to judge a text by the text, it’s what we get from the information contained in the text, it indicates the novelty and diversity that describes the information, which constitute the con bent of the communication in a text. The media indicates the extent to which the elements, and information with in the text are familiar in their meaning, and in the manner in which they are expressed, and the manner in which they are presented, it represents a low-grade media efficiency, or it’s not unusual, it represents high-grade media efficiency. This research deals with the extent to which this criterion between poetry and has been achieved in the art of (dissolution of formulation), which was active in the fourth century AH, by applying it to the book of (AL-Manthur AL-Bahayi), for (AL-Nirmani) (D-414AH), and at the three levels of dissolution of poetry.